Sharia Enterprise Based Control Management and Cultural Control in an Islamic Boarding School - Rahmatika, Armizha; Nafidah, Lina Nasehatun (InFestasi, 2025)
This study aims to assess the revitalization of the management systems of Islamic educational institutions, particularly Islamic boarding schools (Tebuireng), focusing on modernization and declining student numbers. This research is unique in its creation of an internal control system based on the principle of amanah (trust) from Sharia Enterprise Theory (SET), the tension between traditional controls (constraining) and the necessity for adaptive innovation (enabling) is addressed in this research. The outcomes demonstrate that the management system was successfully revitalized by utilizing the amanah principle as a philosophical and practical approach.  This principle instills a direct system of accountability that includes God (the hablunminallah) and people (the hablunminannas), such as parents and donors.  Implementation of strategies involves utilizing diagnostic tools to recognize problems like old buildings) and interactive tools to implement new plans, such as the "Sak Ambané Santri Siji" program for improving infrastructure and the utilization of information systems based on computers for academic endeavors and finances.  As such, the number of students increased significantly, which increased the school's popularity and maintained its status. This approach fosters collaborative and participatory systemic oversight through dialogue.